Motivation for Housewives to Become Content Creators on Facebook Social Media - Rahmadiana Rahmadiana; Tyas Kasusilaningrum; Afwan Wahab (Ikatan Sarjana Komunikasi Indonesia, 2024)
The development of technology and social media has changed the pattern of user participation from passive consumers to active producers. Facebook, with its innovative features such as Reels and paid subscriptions, is becoming a popular platform that encourages users, including housewives, to create content of economic value. This study uses the theory of Uses and Gratifications to analyze the motivation of housewives to use Facebook in meeting social needs, This study uses a qualitative approach with a case study design to explore the experience of housewives as content creators on Facebook. Data were collected through direct observation and in-depth interviews with four informants who met the criteria. Data analysis is carried out by means of data reduction, data presentation, and conclusion drawn. This approach aims to understand the motivation of using Facebook and become a content creator, interaction pattern, and satisfaction for housewives on social media. The results of the study show that housewives use Facebook to meet social, entertainment, information, and economic needs. They build a support network as content creators, creating everyday videos, humor, or tutorials that entertain themselves and their audience. For information needs, they share tips, practical solutions, and product recommendations. Economic motivation also drives them to monetize content for additional income. Facebook is not only a communication tool, but also a platform for social interaction, entertainment, information dissemination, and economic empowerment.